Successful pregnancy after limb-sparing hemipelvectomy for Ewing sarcoma: Case report and literature review - Jun Kakogawa; Masaki Ogawa; Nao Suzuki; Tsutomu Tabata (Elsevier, 2021)
Objective: We present a case of successful pregnancy in a patient who underwent limb-sparing hemipelvectomy combined with multi-agent chemotherapy and radiotherapy for Ewing sarcoma. Case report: A 17-year-old girl was diagnosed with Ewing sarcoma of the left pelvis at the age of 17 and received limb-sparing hemipelvectomy combined with multi-agent chemotherapy and radiotherapy. The patient received oral contraceptives as hormone replacement therapy after completion of treatment. A normal menstruation cycle restored after the withdrawal of oral contraceptives. The patient spontaneously conceived at the age of 25. The patient complained of difficulty walking due to pelvic distortion during pregnancy and delivered a healthy neonate at term by cesarean section. Conclusion: Successful pregnancy and delivery can be achieved after limb-sparing hemipelvectomy combined with chemotherapy and radiotherapy for Ewing sarcoma. Our report provides important information on perinatal management, given the low incidence of pregnancy following treatment of Ewing sarcoma in the pelvis.